Histopathology and Genetic Biomarkers of Choroidal Melanoma - Giuseppe Broggi; Andrea Russo; Michele Reibaldi; Daniela Russo; Silvia Varricchio; Vincenza Bonfiglio; Corrado Spatola; Cristina Barbagallo; Pietro Valerio Foti; Teresio Avitabile; Antonio Longo; Rosario Caltabiano (Applied Sciences, 2020)
Choroidal melanoma (CM), despite its rarity, is the most frequent intraocular malignancy. Over time, several histological variants of CM have been distinguished, including spindle A and B cell, fascicular, epithelioid and necrotic type. However, they have been progressively abandoned as having no prognostic value and currently, the American Joint Committee of Cancer (AJCC) classification identifies three CM cell types: spindle, epithelioid and mixed cell type. Other rare histological variants of CM include: (i) diffuse melanoma; (ii) clear cell; and (iii) balloon cell melanoma. Immunohistochemically, CMs are stained with Human Melanoma Black 45 (HMB45) antigen, S-100 protein, Melan-A (also known as melanoma antigen recognized by T cells 1/MART-1), melanocyte inducing transcription factor (MITF), tyrosinase, vimentin, and Sex determining region Y-Box 10 (SOX10). Several genetic and histopathological prognostic factors of CM have been reported in the literature, including epithelioid cell type, TNM staging, extraocular extension, monosomy 3 and 6p gain and loss of BAP-1 gene. The aim of this review was to summarize the histopathological, immunohistochemical and genetic features of CM, establishing “the state of the art” and providing colleagues with practical tools to promptly deal with patients affected by this rare malignant neoplasm.